Models for forecasting disease development and severity of rubber powdery mildew(Oidium heveae steinm) - Zhoutong Yu; Qianchum Xiao; Shuming Wu; Wuren Huang; Yongqiang Chen (Proceedings of IRRDB Symposium 1999, Hainan, Peoples Republic of China. pp.281-287.)
The disease progress rate is affected by inoculum level at rubber wintering, refoliation speed, temperature, relative humidity during 5;budbrust to 20;refoliation, forecasting models were developed based on these factors, the results of validation in different rubber growing areas on Human Island showed that the forecasting values of the models were rather identical with actual values, and the correlation coefficients were 0.8872-0.9732. The models were used to guide chemical control, the control efficiency was 9.1;higher than normal dusting schedule, 17.6 cost was reduced, and increased 11.4;benefit.
Keywords: Forecasting disease progress; Oidium heveae steinm; Rubber powdery mildew